An Inertial Device-based User Interaction with Occlusion-free Object Handling in a Handheld Augmented Reality - Goh, Eg Su; Sunar, Mohd Shahrizal; Ismail, Ajune Wanis; Andias, Rino (International Journal of Integrated Engineering, 2018)
Augmented Reality (AR) is a technology used to merge virtual objects with real environments in real-time. In AR, the interaction which occurs between the end-user and the AR system has always been the frequently discussed topic. In addition, handheld AR is a new approach in which it delivers enriched 3D virtual objects when a user looks through the device’s video camera. One of the most accepted handheld devices nowadays is the smartphones which are equipped with powerful processors and cameras for capturing still images and video with a range of sensors capable of tracking location, orientation and motion of the user. These modern smartphones offer a sophisticated platform for implementing handheld AR applications. However, handheld display provides interface with the interaction metaphors which are developed with head-mounted display attached along and it might restrict with hardware which is inappropriate for handheld. Therefore, this paper will discuss a proposed real-time inertial device-based interaction technique for 3D object manipulation. It also explains the methods used such for selection, holding, translation and rotation. It aims to improve the limitation in 3D object manipulation when a user can hold the device with both hands without requiring the need to stretch out one hand to manipulate the 3D object. This paper will also recap of previous works in the field of AR and handheld AR. Finally, the paper provides the experimental results to offer new metaphors to manipulate the 3D objects using handheld devices.